Ordovician (middle Darriwilian-earliest Sandbian) conodonts from the Wuhai area of Inner Mongolia, North China. (28th March 2016) - Jing, Xiuchun; Zhou, Hongrui; Wang, Xunlian
Abstract: Forty-two conodont species belonging to 26 genera, which span the middle Darriwilian to the earliest Sandbian interval, are documented from the Wolonggang and Hatuke Creek sections in the Wuhai area of Inner Mongolia, North China. This conodont fauna is dominated by cosmopolitan and widespread species and accompanied by several endemic taxa. Four conodont zones, the Dzikodus tablepointensis, Eoplacognathus suecicus, Pygodus serra, and P . anserinus Zones, and three subzones, the Pygodus lunnensis, P . anitae, and Yangtzeplacognathus foliaceus Subzones, are recognized. Because of its slope habitat, the conodont fauna of Wuhai area differs from the coeval faunas on the North China Platform, which reflect a shallower and warmer water environment, but is similar to the contemporaneous faunas in Baltoscandia, South China, and Tarim. Moreover, the studied sections share several stratigraphically diagnostic taxa with the counterparts of the North China Platform and Western Newfoundland, which makes it an effective link for biostratigraphic correlations both regionally and internationally. The stratigraphically regular occurrences of Spinodus spinatus, a good index of a deep-water environment, represent a Spinodus biofacies that agrees with the Ordovician paleo-tectonic regimes of North China.